PERAN MEDIA SOSIAL DALAM KOMUNIKASI PEMBANGUNAN: ANALISIS KONTEN INSTAGRAM @KATANYASETARA TERHADAP EDUKASI KESETARAAN GENDER DAN PEMBERDAYAAN PEREMPUAN - Aulia Zahrannissa Yunash; Qonita Humaira Fatana (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The gender gap remains a structural issue that continues to hinder women’s participation in various social spheres, ranging from the workplace to everyday community life. Amid the increasingly widespread development of digital technology, social media has emerged as a new tool with great potential to drive changes in public awareness regarding gender issues. This article aims to analyze how the Instagram account @katanyasetara functions as a digital campaign platform to disseminate education on gender equality and women’s empowerment to the Indonesian public, particularly the youngest generation. This study employs a descriptive qualitative method, utilizing data collection techniques such as literature review and content analysis of posts from the @katanyasetara account in Instagram. The results show that @katanyasetara implements effective communication strategies through three main approaches: simplifying complex issues into relatable, non-reachy language, maintaining a consistent visual identity that builds long-term brand recognition, and utilizing contextual case studies closely tied to the audience's real lives to foster empathy and a collective identity. These strategies have proven effective in driving high levels of audience engagement, as evidenced by the positive responses to the analyzed content, including one post that garnered more that 562.000 likes.